Pandora hearts. 24 - Mochizuki, Jun (Yen Press, 2016)
"The players in this tale arrive at the answer to the question of how to save their world, a solution that has traversed time and space. Cruel yet kind, it is a simple formula. Now, led by the cogs of destiny, one story comes to a close ... as if it were no more than a ridiculous fairy tale."--Back cover.